Empirical sigma - d relations and main galactic radio loops - Urošević Dejan V. (Serbian Astronomical Journal, 2002)
This paper represents a review of the empirical Galactic and extragalactic sigma - D relations (relations between the surface brightness sigma and the diameter D) for supernova remnants (SNRs), with checking the connection of the main Galactic radio loops (Loop I, II, III and IV) with these relations. We present results which suggest, in another way, that the radio loops may have an SNR origin. The updated relations have been measured to have slopes beta = 2 in log-log space. The best sigma - D relations for M31 and M33 galaxies were derived and these relations are shown to be flatter (beta < 2) than those for Galactic SNRs alone. This result confirms that selection effects play an important role in data-sets made up of Galactic SNRs. A sigma - D relation with 157 reliable calibrators (both Galactic and extragalactic) is derived. This relation also has a slope beta = 2.07 ± 13.